Measurement of prompt D0, Λ+c, and Σ0,++c (2455) production in proton-proton collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Martin, Nicole Alice; et al. (Physical review letters, 2022)
The pT-differential production cross sections of prompt D0, Λ+c, and Σ0,c(2455) charmed hadrons are measured at midrapidity (|y|<0.5) in pp collisions at √s=13 TeV. This is the first measurement of Σ0,++c production in hadronic collisions. Assuming the same production yield for the three Σ0,+,++c isospin states, the baryon-to-meson cross section ratios Σ0,+,++c/D0 and Λ+c/D0 are calculated in the transverse momentum (pT) intervals 2<pT<12 and 1<pT<24 GeV/c. Values significantly larger than in e+e− collisions are observed, indicating for the first time that baryon enhancement in hadronic collisions also extends to the Σc. The feed-down contribution to Λ+c production from Σ0,+,++c is also reported and is found to be larger than in e+e− collisions. The data are compared with predictions from event generators and other phenomenological models, providing a sensitive test of the different charm-hadronization mechanisms implemented in the models.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol, "0" und "+" sind jeweils hochgestellt, "c" ist jeweils tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M. Kroesen, N. Martin, A. Nath, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S. Stiefelmaier, M. Völkl, B. Windelband, A. Yüncü [und viele weitere]
Gesehen am 17.10.2022